Mapping the Literature on Environmental, Social, Governance, and Bank Performance: A Bibliometric and Content Analysis - Riani, Desmy; Yudhawati, Diah; Hasnin, Hannisa Rahmaniar; Rusydiana, Aam Slamet; Septiyani, Fitria Ika (International Journal of Economics and Financial Issues, 2025)
This study identifies gaps in existing research and proposes ten potential studies based on the most influential publications from the past five years. The study employs bibliometric citation analysis and orange data mining tools to review and analyze 253 documents from Scopus-indexed publications, complemented by content analysis. The analysis highlights a rising focus on the interplay between ESG factors and bank performance within sustainable finance, evidenced by increasing publications and citations. Leading contributors include "Sustainability (Switzerland)" and "Corporate Social Responsibility and Environmental Management." China leads in publication volume, with Amina Buallay as the most influential author. Cluster analysis using the latent Dirichlet allocation model identifies six primary themes. Research gaps are identified, and ten future research directions are proposed based on key publications from the past five years. This research uncovers relatively unexplored clusters with potential for future investigation, providing deeper insights into the advancement of research using statistical data on keyword occurrences with the Orange application. This study relies solely on the Scopus database and specific keywords, which may limit comprehensiveness. Future research should incorporate additional databases and explore individual ESG subthemes in greater depth to provide a more holistic understanding of ESG factors and bank performance.